Medical devices having a matrix adhered thereof. - Domb, Abraham Jackob; Shaulov, Yulia; Levi, Yair; Mandler, Daniel; Tal, Noam. (PCT Int. Appl., 2008)
This invention relates to medical devices having a matrix comprising a pharmaceutically active agent, the matrix being adhered to a surface of the medical device via an adherence to modulate a release of the pharmaceutically active agent. [on SciFinder(R)]
CAPLUS AN 2008:915787(Patent)
Keywords: polymer electrocoating stent